Structural Funds in the European Union and Lithuania - Paškevičienė, Asta; Miškinis, Algirdas (Ekonomika, 2002)
This article deals with the EU Structural and Regional Policies and their financing mechanisms in the EU Member States and Lithuania, as one of the Candidate Countires. Although EU is one of the most prosperous regions in the world, disparities between countries and regions remain visible. To address existing socio-economic disparities between regions, the EU has adopted its structural and regional policies, which, based on financial solidarity of its Member States, aim to promote competitiveness and employment by helping regions to generate sustainable development and adapt to new conditions on the labour market and to global competition. The EU has at its disposal Structural Funds through which it channels financial assistance: the European Regional Development Fund, the European Social Fund, the European Agricultural Guidance and Guarantee Fund and the Financial Instrument for Fisheries Guidance. Support channelled through these funds amount to one third of the European Union’ Budget. In addition, support to four least prosperous Member States infrastructure development is being provided through the Cohesion Fund. The article makes an overview of the main principles of the operation of the Structural Funds and their role in economic development of Member States. The article also deals with three pre-accession instruments: SAPARD, ISPA and Economic and Social Cohesion, which correspond to the main areas of assistance provided through the Structural Funds and imply operational aspects similar to those used by the Structural Funds. In addition, the Article draws conclusions On the effectiveness of structural assistance in the previous years, which may be useful to consider while making transfers to Lithuania under pre-accession instruments and subsequently while programming and receiving transfers through the Structural Funds. The article also draws lessons from the management of Structural Funds and pre-accession facilities for the application in the management of public finances of Lithuania.